A survey of e-participation research projects in the European Union. (9th December 2008) - Tambouris, E.; Kalampokis, E.; Tarabanis, K.
The introduction of Information and Communication Technologies in the field of public participation has led to the emergence of electronic participation (e-participation). The field of e-participation is rapidly evolving and is characterised by an increasing number of related projects and tools. In this paper we survey e-participation projects financially supported by the European Commission under relevant calls for proposals, i.e., within FP5, FP6, eTen, Interreg and the Preparatory Actions 2006. Our results reveal the total investment in e-participation, the main areas of research, as well as the primary technologies and tools in use within these projects.